2020
DOI: 10.1111/jocs.14844
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of tissue versus mechanical aortic valve replacement in patients 50 to 70 years of age

Abstract: Background Societal guidelines suggest that aortic valve replacement (AVR) in patients age 50 to 70 years can be performed with either bioprosthetic or mechanical valves. This study reviewed outcomes between these valve types among patients aged 50 to 70 years undergoing AVR. Methods We examined adult patients 50 to 70 years undergoing isolated AVR with a mechanical or bioprosthetic valve at a single institution between 2010 and 2018. Kaplan‐Meier analysis was used to evaluate longitudinal survival and multiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 20 publications
0
9
1
Order By: Relevance
“…In this study, the surgery group showed numerically higher mortality than that observed in previous studies [ 25 , 26 ]. We assumed that PSM might eliminate the low-risk patients and assign more elderly patients with poor comorbidities to the SAVR cohort than crude analyses.…”
Section: Discussioncontrasting
confidence: 59%
“…In this study, the surgery group showed numerically higher mortality than that observed in previous studies [ 25 , 26 ]. We assumed that PSM might eliminate the low-risk patients and assign more elderly patients with poor comorbidities to the SAVR cohort than crude analyses.…”
Section: Discussioncontrasting
confidence: 59%
“…We also focus on those two aspects in our study. Thirdly, these two analyses were published in 2016 and 2018; several retrospective studies have been published since then, most of which were multi-center and even nationwide, which may provide more accurate results [ 3 , 16 , 23 , 28 , 29 , 32 , 33 ]. Therefore, we conducted this meta-analysis to further compare the clinical outcomes of mechanical and bioprosthetic prostheses in middle-aged patients receiving AVR surgery to give clinicians an update on this topic.…”
Section: Discussionmentioning
confidence: 99%
“… 29 Another group demonstrated in the 50–70 years old cohort that survival at 5 years was higher in patients who had undergone SAVR with mechanical valve versus bioprosthesis and also demonstrated similar freedom from major bleeding events. 31 …”
Section: Discussionmentioning
confidence: 99%
“…29 Another group demonstrated in the 50-70 years old cohort that survival at 5 years was higher in patients who had undergone SAVR with mechanical valve versus bioprosthesis and also demonstrated similar freedom from major bleeding events. 31 Bicuspid aortic valve and aneurysm of the aorta A significant number of patients requiring SAVR have bicuspid aortic valve, which has an incidence of 1%-2% in the general population and may present with aortic valve stenosis, regurgitation and ascending aortic aneurysm. The type of native aortic valve is not recorded in the database of our study.…”
Section: Durability and Choice Of Prosthetic Valvesmentioning
confidence: 99%